Gastronomic potential of food at the maulid sasak tribe event in North Lombok Regency - Farikhatir Rizkiyah, Nurul; Hastuti Nurhayati; Jujuk Ferdianto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Gastronomy is a habit of eating to elements of religious, cultural, social, historical and economic values for a certain community, especially the sasak tribal community in Lombok. This study aims to identify and analyze: (1) Food gastronomic particle and (2) Food gastronomic processing and presentation techniques at the sasak tribal customary maulid event in North Lombok district. This research is a qualitative research and includes field research. This research was carried out in a certain community environment, namely the sasak tribe, especially in the northern Lombok district. The sampling technique is in the form of purposive sampling with special purposes epen gawe, ran, tribal council, and professional chefs in the field of culinary gastronomy. The data collection techniques used are observation, interview and documentation. The data analysis technique used is triangulation by drawing conclusions from the three data collections. The results showed that: (1) The gastronomic efficiency of food served at the sasak tribal traditional maulid event in North Lombok regency is divided into 3 classifications of types of dishes, namely vegetables (side dish), side dishes (main course), and traditional snacks (dessert) and (2) Processing techniques used in processing maulid nabi dishes, namely the deep fry, grill, steam, sautee, boil and simmer. As for serving dishes using a container in the form of a tray (nare) with begibung eating procedures.